Terapeutas ocupacionais e dispositivos grupais na Rede de Atenção Psicossocial - Couto, Ana Carolina Drumond (Universidade Federal de São Carlos, 2023)
The groups developed by Occupational Therapy are devices that trigger the production of psychosocial care, highlighted as relevant by the scientific literature in the area. When taking place in the Sistema Único de Saúde (SUS), the groups gain the dimension of the operationalization of health policies, such as the Política Nacional de Humanização (PNH), based on postures guided by relational technologies, with respect to differences, which trigger the production of autonomy of the participants. The objective was to understand the production of group care from the perspective of Rede de Atenção Psicossocial (RAPS) occupational therapists. This is qualitative research in which a semi-structured interview was conducted with seven occupational therapists, RAPS workers from four regions of Brazil, who carry out groups in their care practice. The treatment of the collected data and its codification took place through Bardin's Content Analysis. Starting from the study of the thematic axis Group Devices and Occupational Therapy, discursive regularities and peculiarities were found that outlined three themes: 1. Care, whose sub-theme is “care production”; 2. Working with groups, with the sub-themes “potentialities for working with groups”, “group as a process” and “method of working with groups”; and, 3. Groups and occupational therapy with the sub-theme “group activities, group activities and workshops”. The occupational therapists participating in this research understand the concept of care as the production of life from the perspective of collective health and pointed out that being an occupational therapist imprints potential to the production of psychosocial care because it is a dynamic and continuously honed practice. In addition, they presented a “being with” that aims at the “walking life” of users beyond institutional walls. From ethical, political and aesthetic postures, they outlined in their reports the roles of coordinators, activators, facilitators and mediators of the groups, paying attention to proceduralities and, therefore, respecting the provisionalities experienced there collectively. It is concluded that, through a creative and live work in action, the occupational therapists point out consonance with the powerful premises of the production of subjectivity, the PNH, the RAPS and the critical and emancipatory occupational therapy.
Occupational therapists and group devices in the Rede de Atenção Psicossocial
Keywords: Prática de grupo; Terapia ocupacional; Política Nacional de Humanização; Atenção Psicossocial; Group device; Occupational therapy; Política Nacional de Humanização; Atenção Psicossocial; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL